Dentin-derived graft for bone healing Integrative sistematic review - Navarro Fernandez, Paula Rocío (2022)
Purpose: The main aim of this study was to perform an integrative review on the effect of the dentin matrix graft for enhanced bone healing. Method: A bibliographic review was performed on PubMed using the following search terms: “dentin” OR “tooth-derived” AND “particle” OR “granule” AND “bone healing” OR “bone repair” OR “bone regeneration” OR “osteoblast”. Studies published in English language until February 28th, 2022 were selected regarding the purpose of this study. Results: The bibliographic search resulted in 23 selected studies in human participants, animals, cell culture, and laboratory research. The chemical treatment of dentin matrix granules involved immersion in different reactive substances such as NaOH or HCl, or HNO3 for partially demineralization of the dentin matrix exposing the collagen fibers, opening the dentin tubules’ diameter, and releasing growth factors. The presence of hydroxyapatite, type I collagen fibers, and proteins (i.e., BMP-2) was detected on the rough surfaces and porous structure of dentin matrix granules. A high proliferation and differentiation of osteogenic cells over dentin matrix granules was recorded in cell culture assays. A higher amount of new bone around dentin matrix granules was recorded in bone defects when compared to non-grafted surgical sites. The amount of new bone was comparable to the sites grafted with demineralized bovine bone mineral. Conclusions: The chemical composition and rough/porous morphological aspects of dentin matrix granules can provide a high bioactivity inducing the migration and adhesion of proteins and osteogenic cells when placed in bone defects. In vivo studies revealed a formation of new bone around dentin matrix granules validating their potential use as alternative bone substitute.